Proceedings, high altitude revegetation workshop no. 4 - Jackson, Charles Leote, 1943-, editor; Schuster, Mark A., editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1980)
The 4th high altitude revegetation workshop was held on February 26-27 at Colorado School of Mines in Golden, Colorado.
June 1980.
Keywords: Revegetation -- United States -- Congresses; Mountain plants -- United States -- Congresses; Tundra plants -- United States -- Congresses; Reclamation of land -- United States -- Congresses